FACTORS ASSOCIATED WITH PATIENTS’ ADHERENCE TO SELF-CARE BEHAVIORS AMONG PATIENTS WITH DIABETES MELLITUS: A LITERATURE REVIEW: LITERATURE REVIEW - Gabby Novikadarti Rahmah; Tintin Sukartini; Sri Utami (Alta Dharma Publisher, 2019)
Diabetes Mellitus is a major public health problem. Adherence to self-care behaviors become one of the factors on diabetes severity. This literature review aimed to identify factors associated with ptients’ adherence to mself-care behaviors among patients with type 2 diabetes mellitus. Articles reviewed in this study were searched using several databases including SCOPUS, EBSCO, Science Direct, SAGE, and CINAHL. Keywords used were “Adherence”,